2017
DOI: 10.1002/joc.4980
|View full text |Cite
|
Sign up to set email alerts
|

Wintertime ENSO influence on late spring European climate: the stratospheric response and the role of North Atlantic SST

Abstract: The impact of the wintertime El Niño‐Southern Oscillation (ENSO) on European late spring climate is examined using an atmospheric general circulation model of intermediate complexity. The analysis is focused on the response of the lower stratosphere/upper troposphere, downward propagation of the ENSO signal detected in temperature, zonal wind and geopotential height and contribution of the North Atlantic to the persistence of the associated surface anomalies. It is found that the stratosphere responds to El Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 68 publications
1
12
0
Order By: Relevance
“…This would agree with LP2015 who found these alternated periods in the signal of EN in Europe in a low-top model, i.e., without a well-resolved stratosphere. This is also consistent with Herceg-Bulic et al (2017) that showed that the persistence of wintertime ENSO signal in both the stratosphere and the North Atlantic is required to enable the delayed ENSO impact on Europe in spring, and Scaife et al (2017) and Knight et al (2017) that highlighted the importance of including tropical Atlantic influence on seasonal forecast to obtain a correct signal of ENSO on Europe. Secondly, analysis of seasonal averages for late winter must be taken with caution because it is a transition season in which different mechanisms might work in different months and the predominant one might mask the rest.…”
Section: Summary and Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This would agree with LP2015 who found these alternated periods in the signal of EN in Europe in a low-top model, i.e., without a well-resolved stratosphere. This is also consistent with Herceg-Bulic et al (2017) that showed that the persistence of wintertime ENSO signal in both the stratosphere and the North Atlantic is required to enable the delayed ENSO impact on Europe in spring, and Scaife et al (2017) and Knight et al (2017) that highlighted the importance of including tropical Atlantic influence on seasonal forecast to obtain a correct signal of ENSO on Europe. Secondly, analysis of seasonal averages for late winter must be taken with caution because it is a transition season in which different mechanisms might work in different months and the predominant one might mask the rest.…”
Section: Summary and Discussionsupporting
confidence: 89%
“…As a second step, the EN-induced polar stratospheric anomalies descend reaching the troposphere in late winter (e.g. : Manzini et al 2006) and inducing a negative NAO phase (Bell et al 2009;Cagnazzo and Manzini 2009;Ineson and Scaife 2009;Herceg-Bulic et al 2017). Most of these studies also showed that the occurrence of a major stratospheric warming (MSW) is essential for the establishment of the aforementioned downward propagation of the EN-induced stratospheric anomalies.…”
Section: Introductionmentioning
confidence: 99%
“…The model has been used to investigate simple troposphere–stratosphere interactions and a discussion around the suitability of the model is provided by Herceg‐Bulic et al (2017), thus showing that it is capable of capturing some key features of the troposphere–stratosphere interaction, despite the low top. The transient eddy heat and momentum flux climatology of the model is presented in Figures S1 and S2 in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…Moron and Gouirand (), King et al (), and Ayarzagüena, Inseon, et al, () suggest that there exists a significantly different teleconnection of ENSO to the Europe/North Atlantic sector in November‐December versus January‐March. Herceg‐Bulić et al () find that the January‐March ENSO response over Europe is maintained by both the stratosphere and extratropical Atlantic SSTs. Jiménez‐Esteve and Domeisen () find that the tropospheric teleconnection across North America that yields a negative NAO for El Niño is present during January‐March, while the signal is limited to February for La Niña, modulated by decadal variability.…”
Section: Enso Teleconnections To the Stratospherementioning
confidence: 99%